PENGARUH EFISIENSI, KEAMANAN, DAN MINAT PENGGUNAAN QRIS TERHADAP INKLUSI KEUANGAN MAHASISWA UNIVERSITAS INSAN BUDI UTOMO - Rima Sampur Tri Wahyuni; Titik Purwanti; Putri Vina sefaverdiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to test and analyze the Efficiency, security and interest in usingQRIS towards financial inclusion of students at Insan Budi Utomo University. Thisstudy is a descriptive quantitative study by distributing questionnaires throughGoogle forms as a method of data collection. The sample in this study was 100respondents, namely students at Insan Budi Utomo University who transacted usingQRIS. The data analysis technique used SPSS ver 25. The results of the studyshowed an R-Square (R ^ 2) value of 0.551, which means that all independentvariables in this study, namely efficiency, security and interest in using QRIS, havea joint contribution, namely 55.1% in the variables efficiency (X1), security (X2),interest in use (X3) and financial inclusion (Y), while the remaining 44.9% isinfluenced by other exogenous variables not used in this study. Hypothesis testingshows that the efficiency of the QRIS non-cash payment system has a positive andsignificant effect on student financial inclusion, security has no effect on financialinclusion with a sig value of 0.110> 0.05, Interest in using QRIS has a positive andsignificant effect on student financial inclusion, Efficiency, security and interest havea simultaneous effect on student financial inclusion with a calculated f value of41.490 with a smaller F table value of 2.698 (41, 490> 2.698) with a significancelevel of 0.000 <0.05 meaning Ho is rejected and Ha is accepted.